Development of Metoprolol Tartrate Sustained Release Formulations by using Modified Starches - Jaswitha, Tirumalasetti (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2021)
This study is aimed to design oral sustained-release formulations for the anti-hypertension drug Metoprolol tartrate. This drug exhibits required physicochemical and pharmacokinetic parameters to formulate sustained-release formulations. The literature survey reveals that Sustained Release formulations for some drugs were prepared by employing Modified Starch known as Calcium Starch. Natural Starches such as potato starch, rice starch, and corn starches can be chemically modified using cross-linking agents such as calcium chloride and it may be used as release retardants. The functional characteristics of starch may vary from source to source. Hence, there is a scope to evaluate the effect of starch on release characteristics of the drug. Further, the drug release is expected to be altered by the proportion of release retardant and hence there is a need to optimize the composition by screening the composition. Hence, there is scope for comparative evaluation of modified starches prepared using different naturally occurring starches and their effect on release characteristics of metoprolol tartrate for sustained release formulations.